2015
DOI: 10.1614/ws-d-15-00053.1
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Basis for Differential Selectivity of Four Grass Species to Aminocyclopyrachlor

Abstract: Aminocyclopyrachlor (AMCP) is a synthetic auxin herbicide used for broadleaf weed control in pasture and rangeland. The tolerance and fate of AMCP within pertinent grass species is not well understood. Research was conducted to establish the tolerance of four grass species to AMCP application and observe their absorption, translocation, and metabolism. Results indicate that tall fescue is the most tolerant of AMCP at rates required for weed control. Bahiagrass and bermudagrass are marginally tolerant, and cogo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…Parker et al (2015) Flessner et al (2011a) found injury consistent with other synthetic auxin-type herbicides that included growth stimulation and vascular inhibition.…”
Section: Invasive Plant Science and Management 85supporting
confidence: 53%
See 1 more Smart Citation
“…Parker et al (2015) Flessner et al (2011a) found injury consistent with other synthetic auxin-type herbicides that included growth stimulation and vascular inhibition.…”
Section: Invasive Plant Science and Management 85supporting
confidence: 53%
“…Although aminocyclopyrachlor primarily controls many broadleaf weeds, certain grasses have also exhibited susceptibility to aminocyclopyrachlor. Parker et al (2015) found I. cylindrica was more susceptible to aminocyclopyrachlor than tall fescue [ Lolium arundinaceum (Schreb.) Darbysh.…”
Section: Resultsmentioning
confidence: 99%
“…japonicus showed a high level of tolerance to mesotrione with no dry weight inhibition at 80 g a.i. ha –1 (data not shown), which may be caused by the different uptake, translocation, and metabolism of herbicides as well as target enzyme sensitivity to herbicides among different weed species. , …”
Section: Resultsmentioning
confidence: 99%
“…Herbicide treatments were applied inside the growth chamber to prevent any outside conditions (wind, differing temperature and humidity) from affecting herbicide penetration and absorption and to restrict observed effects to those originating from environmental factors, limiting any confounding outside effects on target plant physiology and metabolic processes. The application strategy was similar to that used by Parker et al (2015) for absorption experiments. Herbicide treatments were made under separate growth chamber conditions to determine the effect of differing temperature, day/night temperature differential, and humidity on phytotoxicity and hydrogen peroxide formation.…”
Section: Plant Materials and Treatmentsmentioning
confidence: 99%